Preparation of Graft Poly(Arylene Ether Sulfone)s-Based Copolymer with Enhanced Phase-Separated Morphology as Proton Exchange Membranes via Atom Transfer Radical Polymerization - Yang Zhao (Polymers, 2019)
Novel proton exchange membranes (PEMs) based on graft copoly(arylene ether sulfone)s with enhanced phase-separated morphology were prepared using atom transfer radical polymerization (ATRP). A series of PEMs with different graft lengths and sulfonation degrees were prepared. The phase-separated morphologies were confirmed by transmission electron microscopy. Among the membranes prepared and evaluated, PAESPS18S2 exhibited considerably high proton conductivity (0.151 S/cm, 85 °C), benefitting from the graft polymer architecture and phase-separated morphology. The membranes also possessed excellent thermal and chemical stabilities. Highly conductive and stable copoly(arylene ether sulfone)-based membranes would be promising candidates as polymer electrolytes for fuel cell applications.